Analysis and Mapping of Stakeholders in Traditional Use Zone within Marine Protected Area - Roni Bawole (Jurnal Manajemen Hutan Tropika, 2012)
This research is greatly needed in order to accommodate the interest and influence of stakeholders and to find solution to conflict of interests among the stakeholders. As a case study, it was conducted in traditional utilization zone of Cendrawasih Bay National Park (CBNP) at Teluk Wondama Regency from August 2010 to June 2011 using qualitative method. The aim of the research was to formulate pro-and-contra conditions that might have a potential to create conflicts and to find out suitable strategies to resolve the conflicts to improve governance and management. The result shows that most stakeholders are mapped as key players of conflicts interest. The analysis also found that stakeholders were distributed as a subject, key player, and context setter, and no stakeholder was classified as a crowd category. This result implied that most stakeholders have an interests and influences to create good governance and to keep a sustainable development in the traditional use zone. Based on this finding, it can be stated that the existing conflict patterns were categorized as open and latent conflicts. These conflicts can be resolved by creating collaboration among Management Body local community, NGOs, and local government through strengthening the institutional capacity for the management of traditional use zone.